SLANG WORD TYPES IN TWO FAMOUS ENGLISH SONGS OF BLACKPINK - Sari, Wati Purnama (Jurnal Sosial Humaniora dan Pendidikan, 2023)
The aim of the research is to investigate slang word types in two famous English songs of Blackpink entitled “Ice Cream” and “Bet You Wanna”. A descriptive qualitative method is used in this research. Theory of slang words related to speaker-oriented sociological properties advocated by Mattiello (2008) is applied to analyze the data. The research results showed that there are three types of slang words found namely Debasement with 2 data, Group-and subject-restriction with 22 data, and Secrecy and Privacy with 47 data. In conclusion, we can see here that the most used slang words in two famous English songs of Blackpink entitled “Ice Cream” and “Bet You Wanna” is Secrecy and Privacy.